Association of Peripheral Blood Biomarkers With Response to Anti-PD-1 Immunotherapy for Patients With Deficient Mismatch Repair Metastatic Colorectal Cancer: A Multicenter Cohort Study - Cheng, Yi-Kan; Chen, Dong-Wen; Chen, Ping; He, Xiaosheng; Li, Pei-Si; Lin, Zhen-Sen; Chen, Shao-Xia; Ye, Shu-Biao; Lan, Ping (Frontiers in Immunology, 2022)
Purpose: Mismatch repair deficient (dMMR) is an established biomarker for the response to the programmed cell death (PD)-1 inhibitors in metastatic colorectal cancer (mCRC). Although patients with dMMR mCRC could achieve a high incidence of disease control and favorable progression-free survival (PFS), reported response rates to PD-1 inhibitors are variable from 28% to 52%. We aimed to explore the additional predictive biomarkers associated with response to anti-PD-1 immunotherapy in patients with dMMR mCRC. Methods: This multicenter cohort study enrolled patients with dMMR mCRC receiving anti-PD-1 immunotherapy at the Sixth Affiliated Hospital of Sun Yat-sen University and Sun Yat-sen University Cancer Center between December 2016 to December 2019. A total information of 20 peripheral blood biomarkers, including T cells (frequency of CD4+ T cell, frequency of CD8+ T cell, ratio of CD4+/CD8+), carcinoembryonic antigen (CEA), inflammatory markers and lipid metabolism markers, were collected. The association between response or survival and peripheral blood parameters was analyzed. Results: Among the tested parameters, ratio of CD4+/CD8+, frequency of CD4+ T cell was significantly associated with PFS (P=0.023, P=0.012) and overall survival (OS; P=0.027, P=0.019) in univariate analysis. Lower level of CD4+/CD8+ ratio or frequency of CD4+ T cell showed significant association with better overall response rates (ORR; P = 0.03, P=0.01). Ratio of CD4+/CD8+, and frequency of CD4+ T cell maintained significance in multivariate Cox model for PFS (HR=9.23, P=0.004; HR=4.83, P=0.02) and OS (HR=15.22, P=0.009; HR=16.21, P=0.025). Conclusion: This study indicated that the ratio of CD4+/CD8+ and the frequency of CD4+ T cell might be crucial independent biomarkers within dMMR mCRC to better identify patients for anti-PD-1 immunotherapy. If validated in prospective clinical trials, the ratio of CD4+/CD8+ and the frequency of CD4+ T cell might aid in guiding the treatment of PD-1 inhibitors among patients with dMMR mCRC.